Non Linear Control System for Humanoid Robot to Perform Body Language Movements - Gomez-Quispe, J.M.; Pérez-Zuñiga, G.; Arce, D.; Urbina, F.; Gibaja, S.; Paredes, R.; Cuellar, F. (MDPI, 2023)
In social robotics, especially with regard to direct interactions between robots and humans, the robotic movements of the body, arms and head must make an adequate displacement to guarantee an adequate interaction, both from a functional and social point of view. To achieve this, the use of closed-loop control techniques that consider the complex nonlinear dynamics and disturbances inherent in these systems is required. In this paper, an implementation of a nonlinear controller for the tracking of trajectories and a profile of speeds that execute the movements of the arms and head of a humanoid robot based on the mathematical model is proposed. First, the design and implementation of the arms and head are initially presented, then the mathematical model via kinematic and dynamic analysis was performed. With the above, the design of nonlinear controllers such as nonlinear proportional derivative control with gravity compensation, Backstepping control, Sliding Mode control and the application of each of them to the robotic system are presented. A comparative analysis based on a frequency analysis, the efficiency in polynomial trajectories and the implementation requirements allowed selecting the non-linear Backstepping control technique to be implemented. Then, for the implementation, a centralized control architecture is considered, which uses a central microcontroller in the external loop and an internal microcontroller (as internal loop) for each of the actuators. With the above, the selected controller was validated through experiments performed in real time on the implemented humanoid robot, demonstrating proper path tracking of established trajectories for performing body language movements.
Keywords: Humanoid robot; Controller (irrigation); Control theory (sociology); Backstepping; Computer science; Control engineering; Nonlinear system; Kinematics; Robot; Engineering; Artificial intelligence; Adaptive control; Control (management); https://purl.org/pe-repo/ocde/ford#2.02.02